Biscuit Slogan in Commercial Media: An Analytical Exploration of Figurative Language - Sani, Ida Ayu Asri Arda; Suhendra, Erwin; Abdussamad, Zainuddin (Jurnal Ilmu Sosial dan Humaniora, 2024)
This study examines the use of figurative language in biscuit slogans in commercial media, focusing on advertisements from 2015 to 2020. The research aims to explore the linguistic functions of figurative language in advertising and its impact on consumer perception and behavior. A descriptive qualitative research approach is employed, with data collected from fifteen biscuit slogans featured on social media platforms, particularly YouTube. The analysis reveals a variety of figurative language types used in these slogans, including metaphors, symbols, rhetorical questions, assonance, alliteration, repetition, hyperbole, and personification. The findings suggest that figurative language is a powerful tool in advertising, influencing consumer perceptions and brand engagement. The study highlights the importance of cultural elements in slogan creation and the effectiveness of figurative language in making slogans memorable and persuasive. Future research should focus on empirically measuring the impact of figurative language in advertising across different cultural contexts to optimize advertising strategies and enhance brand communication.